Inflation Rate and Poverty Incidence Nexus in Nigeria: Does Lending Rate Moderates The Effect - Isiaka, Najeem Isiaka, Najeem; Olayiwola, Habeeb Olaniyi (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
Poverty incidence is quite high in developing countries, according to the latest data. However, the element that contributes to and mitigates remains a mystery and a source of disagreement in the literature. As a result, the study re-examined the relationship between Nigeria's inflation rate and poverty incidence. It also established the role of borrowing costs in the relationship between inflation and poverty incidence in Nigeria. The analysis spans 40 years, from 1981 to 2020, and secondary data on poverty, inflation, lending, money supply growth, and taxation were culled from World Bank Development Indicators and the Central Bank of Nigeria (CBN) statistical bulletin, 2020 edition. The study used multiple linear regression and an interactive model to achieve the stated objectives. It was revealed that the inflation rate positively correlates with Nigeria's poverty incidence. Also, it was further revealed that the lending rate substantially moderates the inflation rate's positive effect on Nigeria's poverty rate. Therefore, it was concluded that the lending rate is sufficient to change the adverse impact of inflation on the poverty rate within the study under review.  The study recommends that government ensure that inflation is kept at bearable digits while monetary authorities should review upward lending rates to discourage excessive borrowing without productivity.